Synthesis of main chain sulfur-containing aliphatic polycarbonates by organocatalytic ring-opening polymerization of macrocyclic carbonates. Issue 38 (12th September 2019) - Yan, Bingkun; Hou, Jiaqian; Wei, Chao; Xiao, Yan; Lang, Meidong; Huang, Farong
Abstract : The first application of organocatalysts is reported to achieve highly active and living ring-opening polymerization (ROP) of thioether-based macrocyclic carbonates for preparing well-defined main chain thioether functional APCs. Abstract : Main chain thioether functional aliphatic polycarbonates (APCs) with combined attributes of the ROS responsiveness of thioether and biodegradability of APCs have many potential high-value applications much more than those in the biomaterial field. However, the challenges in achieving a well-defined structure and desired functions efficiently hinder the progress of such superior materials. Herein, we describe the first application of organocatalysts to achieve highly active and living ring-opening polymerization (ROP) of thioether-based macrocyclic carbonates for preparing well-defined main chain thioether functional APCs. Of several commercially available catalysts screened, triazabicyclodecene (TBD) can effectively activate the ROP of MS, affording tailor-made thioether functional APCs with high end group fidelity, high molecular weight and narrow molecular-weight distribution. The TBD catalysts present high activity and living polymerization characters, as evidenced by kinetic studies and chain-extension reactions. A category of novel hybrid aliphatic polycarbonates were attained with tunable thioether contents and thermodynamic properties through copolymerization of MS with several cyclic monomers such as trimethylene carbonate (TMC), ε-caprolactone (ε-CL), valerolactone (VL) and lactide (LA), vastly expanding the range of accessible APCs and the application of thioether polymers.